2020
DOI: 10.1038/s41467-020-18799-6
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing a metalloid {Zn12} unit within a polymetallide environment in [K2Zn20Bi16]6−

Abstract: The access to molecules comprising direct Zn–Zn bonds has become very topical in recent years for various reasons. Low-valent organozinc compounds show remarkable reactivities, and larger Zn–Zn-bonded gas-phase species exhibit a very unusual coexistence of insulating and metallic properties. However, as Zn atoms do not show a high tendency to form clusters in condensed phases, synthetic approaches for generating purely inorganic metalloid Znx units under ambient conditions have been lacking so far. Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 71 publications
1
38
0
2
Order By: Relevance
“…27 We recently showed that this solid yields not only said binary anion but also Bi-rich cluster species. 28,45 To expand these studies, we performed reactions in the presence of two mildly Lewis-acidic metal complexes, [La-(C 5 Me 4 H) 3 ] and [Ru(cod)(H 2 CC(Me)CH 2 ) 2 ], which we considered suitable for assisting in the assembly of {Bi n } building units, as the anticipated interaction with the anionic precursor are neither purely ionic nor too strongly covalent. In this way, we obtained single-crystalline compounds [K(crypt-222)] 3.67 [Bi@Ga 8 (Bi •solv (solv = 4.63thf•2en, 3a; solv = none, 3b), comprising the highest bismuth content in clusters reported so far.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 We recently showed that this solid yields not only said binary anion but also Bi-rich cluster species. 28,45 To expand these studies, we performed reactions in the presence of two mildly Lewis-acidic metal complexes, [La-(C 5 Me 4 H) 3 ] and [Ru(cod)(H 2 CC(Me)CH 2 ) 2 ], which we considered suitable for assisting in the assembly of {Bi n } building units, as the anticipated interaction with the anionic precursor are neither purely ionic nor too strongly covalent. In this way, we obtained single-crystalline compounds [K(crypt-222)] 3.67 [Bi@Ga 8 (Bi •solv (solv = 4.63thf•2en, 3a; solv = none, 3b), comprising the highest bismuth content in clusters reported so far.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Scheme 1 summarizes the new findings, which will be discussed in detail below, and all related findings based on the K/Ga/Bi system that were reported previously. 27,28,41,44,45,52 With this study, we contribute to the formation of the largest known consecutively linked polybismuthide architectures and to first insights into the formation of corresponding clusters.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[8c, 9a,c, 12b, 17] The distances from the bases of Sn 8 units to their capped Zn atoms are in a very narrow range of 2.7768-( 18)-2.8014 (18) , comparing well with those of 2.7397(4)-2.7867(4) in [Sn 9 ZnPh] 3À , [9c] 3) ) is only slightly longer than those in [Ge 9 Zn-ZnGe 9 ] 6À (2.420( 1) ) [15] and other monovalent organozinc species (2.305( 3)-2.430( 1) ), [18] but shorter than the Zn-Zn distances (2.544( 3)-2.831( 5) ) in [K 2 Zn 20 Bi 16 ] 6À . [19] To understand the chemical bonding and electronic structure of the investigated cluster, we performed density functional theory (DFT) calculations. All DFT calculations were performed using Gaussian 16 software [20] at PBE0/def2TZVP level of theory.…”
mentioning
confidence: 99%
“…[26][27][28][29][30][31] In contrast to molecules containing (mainly) non-metal atoms where 2-centre-2-electron (2c-2e) bonding dominates (aliphatic and non-aromatic carbon compounds, for example), the increasingly inert nature of the ns electrons in the heavier (semi)metal atoms in Zintl clusters tends to favour electron delocalization and multi-centre-bonding. 83,84 While the finite size of known Zintl clusters (o50 atoms) prevents them from becoming truly metallic on a molecular scale, the typically intense colours (red to brownish black) of salts with sequestrated cations point to narrow HOMO-LUMO gaps. This small band gap can lead to applications in (photo)catalysis, and also makes Zintl clusters precursors of novel nanostructured or doped metals and intermetallic phases.…”
Section: Chemical Properties and Potential Use Of Zintl Clustersmentioning
confidence: 99%